ENHANCEMENT OF HEAT TRANSFER PERFORMANCE OF FLAT VERTICAL TUBE USING SIO2/WATER NANOFLUIDS - Saputra, Eqwar; Surono, Arif; Prasetyo, Andi; Afifah, Dini Nur; Aripin, Janatin Nur (Universitas Muhammadiyah Surakarta, 2026)
This research aims to evaluate the heat transfer characteristics of a radiator using silicon dioxide (SiO2) nanofluid. The study was conducted experimentally, and the research scheme consisted of a water/nanofluid reservoir tank, a heater for water heating, a pump to circulate water/nanofluid to the radiator, and a cooling fan to dissipate heat. The research results indicate a 15% increase in the average heat transfer coefficient at a temperature of 60°C. The maximum heat transfer enhancement occurred at a concentration of 0.2%, with a 21% increase at a Reynolds number of 3200 at a temperature of 60°C. At a temperature of 70°C, there was an 18% increase in the average heat transfer coefficient. The maximum heat transfer enhancement occurred at a concentration of 0.2%, with a 24% increase at a Reynolds number of 3200.